Pengaruh permainan treasure hunt terhadap kemampuan siswa sekolah dasar dalam menganalisis materi arah mata angin - Luthfia Nur Andini; Diah Gusrayani; J Julia (IKIP Siliwangi, 2025)
The current education development is facing challenges, one of which is the students' lack of ability to analyze and understand complex material in real-world context. This study aims to assess the impact of the treasure hunt game on students' ability in analyzing material about cardinal directions. The research method used is a quasi-experiment with a nonequivalent pre-test post-test control group design. The sample consists of two elementary schools: SDN Malaka as the experimental group and SDN Babakanbandung as the control group. The control group used the lecture method, while the experimental group participated in a treasure hunt game designed to enhance their understanding of concept and analytical skills about cardinal directions. The research instrument was in a fotm of an analytical ability test consisting of 20 multiple-choice questions. Data analysis using the t-test showed that the treasure hunt game had a significant impact on students' abilities. The N-Gain test results revealed that the average improvement in analytical ability in the control class was only 11.48% (low category), while in the experimental class it reached 80.00% (high category). Therefore, the treasure hunt game can significantly improve the ability to analyze cardinal directions compared to the lecture method.